2012
DOI: 10.1111/j.1540-8183.2011.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Impact of Prolonged Dual Antiplatelet Therapy after Drug‐Eluting Stent Implantation

Abstract: In this retrospective registry, patients with off-label DES implantation receiving prolonged (>12 months) DAT presented with lower rates of MACCE and myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Ten studies were further eliminated since they were meta-analyses, 11 studies were case studies, 2 studies were protocol of future ongoing trials, 6 articles were letter to editors, and 10 articles were associated with the same trial. Finally, 15 studies (Brar2008 [12], I-LOVE IT 2 [13], ISAR-SAFE [14], Tarantini2016 [15], ARCTIC [16], OPTIMIZE [17], RESET [18], EXCELLENT [3], PEGASUS [19], DAPT [20], Sardella2011 [21], PRODIGY [22], Thukkani2015 [23], ENDEAVOR [24], ITALIC [25]) that satisfied all the inclusion and exclusion criteria of this current analysis, were included. The flow diagram representing the study selection has been illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies were further eliminated since they were meta-analyses, 11 studies were case studies, 2 studies were protocol of future ongoing trials, 6 articles were letter to editors, and 10 articles were associated with the same trial. Finally, 15 studies (Brar2008 [12], I-LOVE IT 2 [13], ISAR-SAFE [14], Tarantini2016 [15], ARCTIC [16], OPTIMIZE [17], RESET [18], EXCELLENT [3], PEGASUS [19], DAPT [20], Sardella2011 [21], PRODIGY [22], Thukkani2015 [23], ENDEAVOR [24], ITALIC [25]) that satisfied all the inclusion and exclusion criteria of this current analysis, were included. The flow diagram representing the study selection has been illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The previous outlined combined risk of disease progression on natural vessels and of increased hazard of ST may explain the differences between our results and previous reported studies, which did not focus specifically on ACS patients treated with PTCA. Many observational studies investigating both stable and unstable patients undergoing stenting reported either positive or neutral results, while randomized clinical trials and the meta‐analysis of Cassese et al did not report a benefit of increased duration of DAPT. However, our results are consistent with the CHARISMA trial, in particular for the subgroup analysis on patients with previous ischemic heart disease: after 2 years, more than 1% reduction in recurrent events was offered by duration of clopidogrel for more than 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…32 When DAPT was discontinued on the physician’s initiative, the duration of treatment before discontinuation ranged from 1 month to 2 years. 8,9,11,1416,18,19,23,26,27,34,36…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported comparative data on cardiovascular mortality (see Supplementary Table 3 online), three of which provided risk analyses (Figure 3). 9,19,27,36…”
Section: Resultsmentioning
confidence: 99%